Comparison of entropy coding mechanism on IEEE1857.2 lossless audio compression standard - Abdul Muin, Fathiah; Gunawan, Teddy Surya; Kartiwi, Mira; Elsheikh, Elsheikh Mohamed Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper has two objectives. First, we aim to review and analyze the performance of the IEEE 1857.2 standard, focusing is on the Golomb-Rice and Arithmetic entropy algorithms as well as the effect of the pre-processing block on these entropy blocks. The pre-processing block normalizes the error residue of the Linear Predictive encoder, which then is passed to Entropy block, where the selector chooses the entropy encoder to use. The second objective is to present results from experimenting different existing algorithms available to benchmark it’. The results are discussed, and comparisons are made to identify the effect on compression ratio and encoding speed of the lossless encoder. As well as this, comparison is made to analyze effects of enabling and disabling the pre-processing output to the Entropy Coding block. We concluded that pre-processing block works well to flatten the output at lower predictor order for all the sound types, but works best at improving the residual output for music sound type.